Development of an asthma risk factors scale (ARFS) for risk assessment asthma screening in children - Souheil Hallit; Chantal Raherison; Diana Malaeb; Rabih Hallit; Mirna Waked; Nelly Kheir; Pascale Salameh (Elsevier, 2019)
Background: The study objective was to create asthma risk factors scale (ARFS) score that would be correlated with the increased risk of asthma in Lebanese children. This scale would eventually be used both to identify children at risk and assess early diagnosis of asthma. Methods: A case-control study (study 1) of 1276 children (976 controls and 300 cases) and a cross-sectional study (study 2) of 1000 children were conducted using a parental questionnaire. Children aged between 3 and 16 years were screened for possible enrollment. The ARFS was created by combining the following risk factors: child's exposure to pesticides, detergent mixing, alcohol, smoking and drug intake during pregnancy and breastfeeding, the actual paternal and maternal smoking status and history of asthma, and the types of food the child consumes. Results: There was a significant increase in the risk assessment screening for asthma per 15 points increments of ARFS (p < 0.001 for trend). The score category 0-14.99 best-represented control individuals (88.8% controls), while a score higher than 45 represented asthmatic children best (98.4% asthmatics). The positive predictive value (disease positive/all positive by scale) came out as 94.02%, whereas the negative predictive value (disease negative/all negative by scale) was found to be 90.47%. These results were confirmed in the second study sample. Conclusion: The ARFS is a simple and easy-to-use tool, composed of 15 questions, for the clinician risk assessment of asthma in children, taking into account the environmental exposure, parental history of asthma and dietary habits of the child. Its value for asthma diagnosis remains to be confirmed in future prospective studies, especially in children with chronic respiratory symptoms. Key Words: asthma, asthma risk factors, children, cumulative risk, environmental factors